Non-infective cystitis secondary to benralizumab immunotherapy. Issue 1 (17th January 2022) - Murray, Toby; Haagsma, Ben; Chetwood, Andrew
Abstract : This case study discusses a patient who presented with severe lower urinary tract symptoms and pain after commencing immunotherapy for eosinophilic asthma. Initial aetiology was presumed to be infective but cultures were negative. Cross-sectional imaging showed extensive perivesical and periprostatic stranding and inflammation. He was initially treated with antibiotics and anti-inflammatories but a lack of clinical improvement led to a rigid cystoscopy which identified an inflamed, oedematous urothelium which was biopsied. Histology demonstrated extensive, full thickness superficial detrusor inflammation, with marked congestion, oedema and a mixed inflammatory infiltrate in keeping with a severe active chronic non-infectious cystitis, possibly secondary to benralizumab therapy. His benralizumab was stopped and his symptoms completely settled. We believe this is the first described case of severe non-infective cystitis which may be secondary to benralizumab. This case adds to the isolated reports of this rare side effect of some of the newer biological agents in use.